The Food and Water Hygiene as Critical Determinants Of Diarrheal Disease: An Epidemiological and Environmental Health Risk Assessment in Payakumbuh City, Indonesia - Anisa, Lisa; Akbarullah, Akbarullah; Barlian, Eri; Yuniarti, Elsa; Handayuni, Linda; Ridha, Mhd (Postgraduate School, Universitas Negeri Padang, 2025)
Diarrheal disease remains a persistent public health challenge in Indonesian municipalities despite substantial improvements in basic sanitation infrastructure. This comprehensive review synthesizes epidemiological data, microbiological water quality assessments, and environmental health risk factors to elucidate the complex pathways linking water safety, sanitation practices, and disease incidence. Examining municipal surveillance data from Payakumbuh City, West Sumatra (2020–2024), we document a 24.3% reduction in reported diarrheal cases concurrent with modest improvements in municipal water quality metrics. However, critical sanitation vulnerabilities persist, with 10.8% of households maintaining reliance on microbiologically contaminated wells (mean E. coli: 3,367 CFU/100mL), and 65.2% of septic tank systems never receiving professional emptying. Spatial risk mapping reveals that 85.1% of municipal subdistricts face high-to-very-high wastewater management hazards despite 78.4% coverage by piped water systems. This investigation demonstrates that the discrepancy between aggregate infrastructure coverage and micro-level sanitation quality represents the principal challenge in tropical urban settings. Targeted interventions addressing critical gaps in septage management, household-level water treatment, and behavioral hygiene transformation are necessary to accelerate disease reduction. The integration of Environmental Health Risk Assessment (EHRA) methodologies with epidemiological surveillance provides an evidence framework for prioritizing resource allocation in resource-limited settings.